The Therapeutic Efficacy of Danhong Injection Combined With Percutaneous Coronary Intervention in Acute Coronary Syndrome: A Systematic Review and Meta-Analysis - Zou, Jun-Bo; Zhang, Xiao-Fei; Wang, Jing; Wang, Fang; Cheng, Jiang-Xue; Yang, Fang-Yan; Song, Xiao; Wang, Yu; Liang, Yu-Lin; Shi, Ya-Jun (Frontiers in Pharmacology, 2018)
Background: Percutaneous Coronary Intervention (PCI) is widely used in treatment of Acute Coronary Syndrome (ACS) clinically. It is believed that Danhong Injection (DHI) extracted from salviae miltiorrhizae and flos carthami combined with PCI could increase the therapeutic efficacy on ACS. We provide an updated meta-analysis with detailed information on combination of DHI and PCI therapy. Materials and Methods: Electronic databases were searched for appropriate articles without language limitations on key words before October 22, 2017. All trails were screened according to certain criteria. Quality of eligible studies was also assessed. We made a detailed record of outcome measurements. RevMan 5.3 software was used to perform the meta-analysis. Results: 14 articles involving 1533 patients with ACS were selected. Compared to PCI treatment alone, Total efficacy rate (TER) was enhanced and major adverse cardiovascular events (MACE) were reduced significantly for the combination of DHI and PCI (P < 0.00001). Vascular endothelial function was improved by significantly decreasing the contents of ET-1, vWF and increasing the levels of NO and FMD (P < 0.00001). The serum levels of IL-1, IL-6, IL-18, TNF-α, LpPLA2, MMP-9 and pentraxin-3 were significantly decreased (P < 0.00001), whereas IL-10 in serum was increased (P < 0.00001), indicating a stronger anti-inflammatory effect of the combination. The combination therapy decreased the serum levels of CD62P, PAGT, PADT, FIB-C significantly (P < 0.05), which was beneficial for preventing coagulation of platelets. Blood lipid was also affected by regulating TC, TG, LDL and HDL, but the results were not statistically significant (P > 0.05). Cardiac function was improved by increasing LEVF (P = 0.006) but not LVED (P = 0.08). The combination treatment was associated with an improvement in antioxidant effect by decreasing MDA and increasing SOD significantly (P < 0.00001). Conclusion: Combination of DHI and PCI in treatment of ACS could improve TER and reduce incidence of MACE after PCI therapy. These effects may be mediated by combined actions of several mechanisms. However, these results of this study should be handled cautiously due to the limitations of this research. Several rigorous RCTs are in need to confirm these findings.